WHATSAPP MEDIA IN ONLINE LEARNING DURING COVID-19 PANDEMIC - Dewi suriyani Djamdjuri; Atiyatul Kamilah (ENGLISH, 2020)
Since early of 2020 the world has been hit by a virus called the corona virus which was originated from the city of Wuhan, China. Corona virus is a microorganism that causes respiratory problems starting from mild to severe symptoms, the incubation or quarantine period is between 6 to 14 days. All activities are stopped, one of which is the Educational Institution. Schools cannot be implemented face-to-face, but schools must continue to run. Therefore, the Minister of Education and Culture of the Republic of Indonesia through Permendikbud No. 4 of 2020 provides a policy on a series of learning in an emergency situation of the spread of Covid-19, namely distance learning (PJJ) or online learning. Online learning using WhatsApp or the Learning Management System (LMS) media are almost used by teachers and students. This study uses a qualitative method to determine which platforms / media are easily accessible for online learning. The result shows that WhatsApp media is very easy to use in online learning during the pandemic-19. There is 75 % of the respondents use WhatsApp as learning media and only 25 % use LMS. In otherwise, some teachers also stated that online learning felt less effective because of internet signals and data.